Structural health of a road tunnel intersecting a large and active rock-block slide - Festi, Pietro; Bossi, Giulia; Francioni, Mirko; Marcato, Gianluca; Staboli, Chiara; Borgatti, Lisa (Italian journal of engineering geology and environment, 2023)
This work presents the case study of the San Lorenzo road tunnel, a linear infrastructure located in Friuli Venezia Giulia, northern Italy, affected by the so-called Passo della Morte landslide. This slope instability phenomenon has caused several problems since the beginning of the tunnel construction works, like water seepage and concrete lining detachments, increasing the safety risk for road users. Due to these circumstances, numerous studies have been conducted and a monitoring system has been developed since 2014 to control the ongoing situation of the most damaged portions of the road tunnel. Building on the monitoring data, studies and knowledge accumulated over the years, this paper describes the work done to trace back the sum of landslide-induced stresses directly responsible for the current damages on the tunnel. The first steps taken in this direction have included an adequate representation of the crack pattern on the tunnel vault. This has been used both as an initial goal and as a means of validation in the development of a finite element model. From the latter, it will be possible to infer the landslide-induced stress combination mentioned earlier.